Iatrogenic late preterm birth: when is it recommended? A Delphi survey promoted by the Italian Society of Perinatal Medicine. (September 2019) - Monari, F; Parazzini, F; Cetin, I; Ballarini, M; Facchinetti, F
Abstract: Background: The rate of iatrogenic Late Preterm (LP) Birth varies in different settings. This is due to the lack of strong evidence/guidelines on the management of the different maternal, fetal and placental complications affecting pregnancy in the LP window. Steroid prophylaxis is also under discussion. Aim: To build recommendations about the management of main medical complications (pregestational diabetes, placenta previa, preeclampsia, cholestasis, p-PROM, intrauterine growth restriction -IUGR-) occurring in the LP period to reduce clinical heterogeneity. Methods: A group of Italian Perinatal experts were identified by Scientific Societies. A Delphi consensus methodology was used to reach agreement on different clinical sceneries. Two rounds of consultation by using a purpose built on-line survey and a third open panel discussion were performed. Results: The panel of 50 experts reached agreement for the vast majority of clinical sceneries (Placenta Previa, Preeclampsia, Diabetes, Cholestasis). Overall, there was agreement to be conservative at 34 weeks and in favor of delivery at 36 weeks. The management of p-PROM and mostly of IUGR were characterized by a minor degree of consensus. Corticosteroids were found necessary at the 34th week and unnecessary at the 36th week. Conclusions: Besides providing some guidance on clinical indications for LP iatrogenic delivery, these results represent a stimulus for designing future trials investigating the grey areas in this field.